2021
DOI: 10.3389/fnins.2021.716476
|View full text |Cite
|
Sign up to set email alerts
|

Memory Deficit in Patients With Temporal Lobe Epilepsy: Evidence From Eye Tracking Technology

Abstract: Objective: To explore quantitative measurements of the visual attention and neuroelectrophysiological relevance of memory deficits in temporal lobe epilepsy (TLE) by eye tracking and electroencephalography (EEG).Methods: Thirty-four TLE patients and twenty-eight healthy controls were invited to complete neurobehavioral assessments, cognitive oculomotor tasks, and 24-h video EEG (VEEG) recordings using an automated computer-based memory assessment platform with an eye tracker. Visit counts, visit time, and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The automated computer-based memory assessment platform was adapted from Li et al as reported in our previous study, 24 The subjects were asked to acknowledge the memory target(s) by clicking a mouse. They were prompted for a response and after their response was recorded, feedback was provided and they clicked the left mouse button to continue to the next trial.…”
Section: Game Designmentioning
confidence: 99%
“…The automated computer-based memory assessment platform was adapted from Li et al as reported in our previous study, 24 The subjects were asked to acknowledge the memory target(s) by clicking a mouse. They were prompted for a response and after their response was recorded, feedback was provided and they clicked the left mouse button to continue to the next trial.…”
Section: Game Designmentioning
confidence: 99%
“…[21][22][23] Based on these, we can unfold the pattern of memory encoding and recognition, and elucidate the underlying mechanism of memory deficits in the diseases. 22,24 The visual paired comparison (VPC) task has been validated as a widely scalable discriminant digital cognitive assessment, especially in recognition memory. 20,25 In this task, subjects are familiarized with two identical images followed by the presentation of the familiar image coupled with a novel one.…”
Section: Introductionmentioning
confidence: 99%
“…Memory has been shown to guide eye movements, which might enhance the efficiency of visual exploration by directing attention toward informative regions 21–23 . Based on these, we can unfold the pattern of memory encoding and recognition, and elucidate the underlying mechanism of memory deficits in the diseases 22,24 . The visual paired comparison (VPC) task has been validated as a widely scalable discriminant digital cognitive assessment, especially in recognition memory 20,25 .…”
Section: Introductionmentioning
confidence: 99%
“…19,23 Eye movements are closely associated with attentional behavior in the normative state [24][25][26] and demonstrate marked abnormalities in people with epilepsy. [27][28][29][30][31] The strong associations between eye movements and attentional behavior provide a compelling rationale to apply eye tracking as an adjunct in the neuropsychological assessment of children with epilepsy. 31,32 Furthermore, because eye movements can be tracked on a moment-to-moment basis, they may inform understanding of ephemeral processes, such as TCI.…”
Section: Introductionmentioning
confidence: 99%
“…Eye movements are closely associated with attentional behavior in the normative state 24–26 and demonstrate marked abnormalities in people with epilepsy 27–31 . The strong associations between eye movements and attentional behavior provide a compelling rationale to apply eye tracking as an adjunct in the neuropsychological assessment of children with epilepsy 31,32 .…”
Section: Introductionmentioning
confidence: 99%